Fresno Merced Counties Legal Services Potluck With Social Security Appeals - Watkins, Howard::::::::: (1982)
Office staff: Virginia Salmeron, Eddie Mae Lomack, friend, Norma Sigala, Michael Kanz, Bob Higgins, Leroy Cordova, Janie Munoz